The impact of the war in Ukraine on the physical and sexual development of girls with menstrual disorders - V.O. Dynnik; O.O. Dynnik; O.G. Verhoshanova; A.Ye. Druzhynina; H.O. Havenko; S.V. Novokhatska (Zdorovʹe Rebenka)
Background. Puberty and the formation of menstrual function are significant stressors for a girl. Traumatic war experience can deepen maladaptive reactions of the body and lead to more serious consequences of menstrual disorders. The purpose of the study was to investigate the features of changes in physical and sexual maturation in girls with menstrual disorders under the influence of a long stay in a front-line city. Materials and methods. One hundred and fifty-three adolescent girls aged 11–18 years were examined, including 69 patients with abnormal uterine bleeding (AUB) and 84 with oligomenorrhea (OM), who resided in a front-line city. The comparison group was girls with similar menstrual disorders who were treated at the pediatric gynecology department of the State Institution “Institute for Children and Adolescents Health Care” in 2019–2021. Clinical anthropometry was performed to assess physical development, and body mass index was calculated. The main indicators of sexual maturation were the degree of development of secondary sex characteristics (breast development, pubic and axillary hair), and the time of onset of the first menstruation. Results. Slightly more than half of the girls with OM (51.9 %) and a third with AUB (37.1 %) had growth within the normative values before the start of the full-scale war. During the war, a tendency to decrease these indicators was noted. Among the deviations both before and during the war, precocious puberty and tall stature prevailed. Stay in the combat zone leads to a decrease in the proportion of adolescents with physiological body mass index. The number of girls with excess body weight and obesity is significantly increasing (in AUB, from 16.7 % before the war to 32.4 % during the war, P < 0.001; in OM, from 12.3 % before the war to 33.3 % during the war, P < 0.0001). A significant increase in precocious puberty among 11–13-year-old girls has been recorded (in AUB, from 75 % before the war to 83.9 % during the war, P < 0.05; in OM, from 38.5 % before the war to 92.3 % during the war, P < 0.000001). The age of menarche has probably decreased due to early menarche (in AUB, the percentage of girls with early menarche in relation to the total number of those surveyed increased from 18.2 % before the war to 31.9 % during the war, P < 0.01; in OM, from 8.5 % before the war to 14.3 % during the war, P < 0.02). Conclusions. The physical and sexual development of girls with menstrual disorders are among the most important indicators of the impact of stress on the body, which can be used as the main, most evident and reliable criteria for the adverse course of menstrual disorders against the background of war.